2014
DOI: 10.1007/s11524-014-9865-8
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of the Repeal of Missouri’s Handgun Purchaser Licensing Law on Homicides

Abstract: In the USA, homicide is a leading cause of death for young males and a major cause of racial disparities in life expectancy for men. There are intense debate and little rigorous research on the effects of firearm sales regulation on homicides. This study estimates the impact of Missouri's 2007 repeal of its permit-to-purchase (PTP) handgun law on states' homicide rates and controls for changes in poverty, unemployment, crime, incarceration, policing levels, and other policies that could potentially affect homi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
86
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(95 citation statements)
references
References 19 publications
4
86
0
Order By: Relevance
“…Across three studies, all found these laws to be associated with increases in homicide rates, and two of the estimates were statistically significant. The median effect size across these studies was 1.10 (Cheng and Hoekstra, 2013;Humphreys, Gasparrini, and Wiebe, 2017;Webster, Crifasi, and Vernick, 2014). Stand your ground laws were one of the few types of policies on which experts estimated effects in opposite directions.…”
Section: Experts' Estimates Of the Probable Effects Of Policies Are Bmentioning
confidence: 99%
“…Across three studies, all found these laws to be associated with increases in homicide rates, and two of the estimates were statistically significant. The median effect size across these studies was 1.10 (Cheng and Hoekstra, 2013;Humphreys, Gasparrini, and Wiebe, 2017;Webster, Crifasi, and Vernick, 2014). Stand your ground laws were one of the few types of policies on which experts estimated effects in opposite directions.…”
Section: Experts' Estimates Of the Probable Effects Of Policies Are Bmentioning
confidence: 99%
“…Finally, a comprehensive requirement that firearm sales and transfers of other types involve a background check on the recipient would help prevent prohibited persons from acquiring firearms anonymously and illegally from private parties, including via the Internet. Background checks are effective (54,58,60,63,64) and, again, widely supported (1, 11,19,22,49,67).…”
Section: Figure 11mentioning
confidence: 99%
“…The most recent change was Missouri's 2007 repeal of its PTP handgun law. Webster et al studied the effects of this policy on lethal violence with a 50-state panel study using data for the period 1999-2012 (43). Regression analyses controlled for state and year fixed effects and changes in unemployment, poverty, policing levels, incarceration, burglary rates (as a general measure of crime), and policies concerning the ease of getting concealed weapons permits, junk gun bans, and so-called "Stand Your Ground" laws.…”
Section: Wwwannualreviewsorg • Firearm Policies For High-risk Personsmentioning
confidence: 99%